Motion planning for a multi-arm surgical robot using both sampling-based algorithms and motion primitives - Preda, Nicola; Manurung, Auralius; Lambercy, Olivier; Gassert, Roger; Bonfe, Marcello (2015 IEEE RSJ International Conference on Intelligent Robots and Systems (IROS), 2015)
The paper describes a motion planning and control software architecture developed for the automation of a surgical robot. The considered surgical robot is a dual-arm prototype developed with a redundant and modular mechanical structure, designed to be reconfigured for different surgical tasks, and with a hybrid parallel/serial kinematics. The motion planning solution proposed in the paper includes both an online collision-free path planner, based on the RRT-Connect algorithm, and a generator of predefined motion primitives. This solution allows the multi-arm robot to autonomously execute the complex motion patterns required for a suturing task. Since such motion patterns are specified in the Cartesian space, an efficient and univocal solution of the inverse kinematics of the robot, which is a challenging problem due to its hybrid structure, is another crucial issue addressed in the paper.